6 | = | x |

| |

1 | 2 |

Cross multiply:
6 * 2 = 1 * x
Simplifying
6 * 2 = 1 * x
Multiply 6 * 2
12 = 1 * x
Solving
12 = 1x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-1x' to each side of the equation.
12 + -1x = 1x + -1x
Combine like terms: 1x + -1x = 0
12 + -1x = 0
Add '-12' to each side of the equation.
12 + -12 + -1x = 0 + -12
Combine like terms: 12 + -12 = 0
0 + -1x = 0 + -12
-1x = 0 + -12
Combine like terms: 0 + -12 = -12
-1x = -12
Divide each side by '-1'.
x = 12
Simplifying
x = 12